The Sachet Telecom Architecture for Off Grid Locations: An Indian Case Study - Prasad, Rohit; Mehrotra, Rakesh (International journal of business data communications and networking, 2012)
In the light of past attempts to provide universal access to telephony and data connectivity, this paper outlines a new telecom architecture tailored to the needs of rural areas, the Sachet Telecom technology. It presents an economic model for an Indian state, Rajasthan, showing the Sachet Telecom architecture, besides empowering local entrepreneurs, scores over the conventional approach in commercial and environmental terms. The approach has the potential to be replicated for rural voice and data connectivity in energy starved regions across the world and can act as a bridge to prepare the population for the coming of fibre networks.